Performance of Random Linear Coding Over Multiple Error-Prone Wireless Links - Garrido, Pablo; Gomez, David; Aguero, Ramon; Munoz, Luis (IEEE communications letters, 2015)
In this letter we derive an exact formulation for the performance of Random Linear Coding (RLC) when applied over multiple wireless links. We combine this technique with UDP so as to offer a reliable communication service . We extend a previous result, which only considered one single link, to embrace both multiple sources as well as varying quality of wireless links. We establish the number of excess packets that are required to successfully accomplish the communication and, based on the Bianchi model, we calculate the achieved throughput. We also propose a context-aware probabilistic transmission scheme that leads to a relevant performance gain. We use a thorough simulation-based study over the ns-3 framework to assess the validity of the proposed model and to broaden the corresponding analysis.